Effectiveness of relapse prevention therapy on psycho–social parameters among individual and dyadic group alcohol dependents - Mrs.VANITHA INNOCENT RANI; Dr.J.VENKATESAN; Dr,R.VIJAYARAGAVAN (International Journal of Pharma and Bio Sciences, 2017)
The effectiveness of RPT on bio-psycho –social parameters among 240 alcohol dependents were done in selected de-addiction centres at Thanjavur district. The 120 samples were in experiment and 120 were in control group. Samples were selected by using the consecutive sampling Technique. Quasi- experimental pre test – post test control group design were used. Data collected through interview method using 1 standardized Questionnaires and 1 semi –structured questionnaire was then used to assess the psycho-social parameters. The obtained paired ‘T’ test score had significant effect on ‘P’ Value < 0.05 in psycho-social parameters in experimental group. It indicates the given RPT was effective in both IAD & DAD. There was a highly positive significant correlation in experimental group. The obtained unpaired ‘T’ test score for comparison between experimental and control groups showed a significant difference in Psycho-Social parameters of the experimental group alone .The comparison between IAD & DAD group had significant difference in psycho-social parameters of the experimental groups. Hence the study result revealed that RPT was effective for the experimental groups. And RPT with Care givers support was more effective in DAD experimental group. So RPT with care givers support was more effective on psycho-social parameters of alcohol dependents.